PENGARUH TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN STUDI KASUS PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BEI 2008 – 2012 - Arief Raharjo; Indira Djanuarti (Diponegoro Journal of Accounting, 2014)
Corporate social responsibility is the companies commitment to support the realization of sustainable development. Legitimacy theory explains that social responsibility disclosure to obtain the legitimacy where the companies located. The legitimact will increase corporate reputation,  That will eventually affect the firm value. Data collection method using pursosive sampling method for listed mining companies in Indonesian Stock Exchange during 2008 until 2012. The result of this research show that corporate social responsibilities give positive effect toward firm value.